Interaction of calcium responsive proteins and transcriptional factors with the PHO regulon in yeasts and fungi - Martín, Juan F. (Frontiers in Cell and Developmental Biology, 2023)
Phosphate and calcium ions are nutrients that play key roles in growth, differentiation and the production of bioactive secondary metabolites in filamentous fungi. Phosphate concentration regulates the biosynthesis of hundreds of fungal metabolites. The central mechanisms of phosphate transport and regulation, mediated by the master Pho4 transcriptional factor are known, but many aspects of the control of gene expression need further research. High ATP concentration in the cells leads to inositol pyrophosphate molecules formation, such as IP3 and IP7, that act as phosphorylation status reporters. Calcium ions are intracellular messengers in eukaryotic organisms and calcium homeostasis follows elaborated patterns in response to different nutritional and environmental factors, including cross-talking with phosphate concentrations. A large part of the intracellular calcium is stored in vacuoles and other organelles forming complexes with polyphosphate. The free cytosolic calcium concentration is maintained by transport from the external medium or by release from the store organelles through calcium permeable transient receptor (TRP) ion channels. Calcium ions, particularly the free cytosolic calcium levels, control the biosynthesis of fungal metabolites by two mechanisms, 1) direct interaction of calcium-bound calmodulin with antibiotic synthesizing enzymes, and 2) by the calmodulin-calcineurin signaling cascade. Control of very different secondary metabolites, including pathogenicity determinants, are mediated by calcium through the Crz1 factor. Several interactions between calcium homeostasis and phosphate, have been demonstrated in the last decade: 1) The inositol pyrophosphate IP3 triggers the release of calcium ions from internal stores into the cytosol, 2) Expression of the high affinity phosphate transporter Pho89, a Na+/phosphate symporter, is controlled by Crz1. Also, mutants defective in the calcium permeable TRPCa7-like of S. cerevisiae shown impaired expression of Pho89. This information suggests that CrzA and Pho89 play key roles in the interaction of phosphate and calcium regulatory pathways, 3) Finally, acidocalcisomes organelles have been found in mycorrhiza and in some melanin producing fungi; that show similar characteristics as protozoa calcisomes. In these organelles there is a close interaction between orthophosphate, pyrophosphate and polyphosphate and calcium ions that are absorbed in the polyanionic polyphosphate matrix. These advances open new perspectives for the control of fungal metabolism.